2002
DOI: 10.1088/0953-2048/15/3/329
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties and ultrasonic attenuation of TlSr2(Sr0.5Y0.5)Cu2O7superconductors

Abstract: The elastic properties and ultrasonic attenuation of TlSr 2 (Sr 0.5 Y 0.5 )Cu 2 O 7 have been determined between 80 and 280 K at frequencies in the 10 MHz region. Electrical resistance versus temperature measurement showed that the critical temperature is 88 K. Ultrasonic measurements showed a change in longitudinal velocity gradient and the attenuation peak around 200 K. The results were explained in terms of the phase transition associated with local oxygen ordering. The shear velocity showed an almost monot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…[8] showed similar step-like elastic anomalies above 230 K. In the present work, the existence of the step-like elastic anomaly was suggested to be due to some form of oxygen ordering taking place in TlÀO planes. A similar explanation was reported for other Tl1212 samples such as TlSr 2 (Ca 1¡x Pr x )Cu 2 O 7¡d , [13] TlSr(Sr 1¡x Y x )Cu 2 O 7 [12] and TlSr 2 (M 1¡x Y x )Cu 2 O 7 (M D Ca, Sr), [11] where it was suggested that the step-like elastic anomaly reflects the possibility of structural distortion of TlÀO planes related to the existence of short-range oxygen ordering in TlÀO (3) superstructures. In these samples, differences in oxygen content may not be the main factor affecting the results as the same preparation condition was used.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…[8] showed similar step-like elastic anomalies above 230 K. In the present work, the existence of the step-like elastic anomaly was suggested to be due to some form of oxygen ordering taking place in TlÀO planes. A similar explanation was reported for other Tl1212 samples such as TlSr 2 (Ca 1¡x Pr x )Cu 2 O 7¡d , [13] TlSr(Sr 1¡x Y x )Cu 2 O 7 [12] and TlSr 2 (M 1¡x Y x )Cu 2 O 7 (M D Ca, Sr), [11] where it was suggested that the step-like elastic anomaly reflects the possibility of structural distortion of TlÀO planes related to the existence of short-range oxygen ordering in TlÀO (3) superstructures. In these samples, differences in oxygen content may not be the main factor affecting the results as the same preparation condition was used.…”
Section: Discussionsupporting
confidence: 85%
“…[11À13] For instance, substitution of Y 3C in TlSr(Sr 2¡x Y x )Cu 2 O 7¡d [12] shows step-like elastic anomaly indicating pronounced lattice hardening around 230 K. The appearance of the elastic anomaly was suggested to involve some form of oxygen ordering taking place at TlÀO planes.…”
Section: Introductionmentioning
confidence: 99%
“…The weak anomaly which was characterized by slowing down of hardening rate, but which does not seem to amount to a softening, is a signal of nucleation of a phase transition where oxygen ordering begins to take place. Previous reports on step-like elastic anomalies observed in other Tl-based samples such as TlSr 2 (Ca 1 À x Pr x )Cu 2 O 7 À δ [6], TlSr(Sr 1 À x Y x )Cu 2 O 7 [23] and TlSr 2 (M 1 À x Y x )Cu 2 O 7 (M ¼Ca, Sr) [22] reflects the possibility of structural distortion of Tl-O planes and is attributed to existence of short-range ordering in the Tl-O(3) superstructures. On the other hand, the Cd substitution shows increase in slope change of the step-like anomaly from 0.0091 GPa/K to 0.0791 GPa/K (x ¼0.3) before decreasing to 0.0569 GPa/K (x ¼0.4) (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, Tl1212 is iso-structural to the YBa 2 Cu 3 O 7 À δ system [21] and temperature dependence of sound velocity in samples showed strong influence of the substitutions on elastic behavior. For instance, for [22], longitudinal velocity measurements revealed step-like elastic anomaly indicating pronounced lattice hardening around 230 K. The existence of elastic anomaly in the sample has been proposed to correspond to some kind of oxygen ordering taking place in Tl-O planes [6,22,23]. However, compared to RE123 reports on ultrasonic measurements on Tl-based were quite limited.…”
Section: Introductionmentioning
confidence: 96%